La presencia del inglés en la publicidad televisiva española (2013-2015): Goretti García Morales, María Isabel González Cruz, Carmen Luján García y María Jesús Rodríguez Medina Madrid: Síntesis, 2016. - Crespo-Fernández, Eliecer (Miscelánea: A Journal of English and American Studies, 2016)
.